OPTIMASI ALOKASI AIR WADUK MENINTING UNTUK PENINGKATAN SUPLESI AIR IRIGASI SALURAN HLD JANGKOK-BABAK-JURANG SATE: indonesia - Sugiharta Sugiharta; Restusari Evayanti (J-ENSITEC, 2022)
To increase the allocation of water in the river basin (WS) of southern Lombok, the potential for irrigation areas (AI) has spread widely, since the 1980s, efforts have been made to transfer water from wet river basins to dry watersheds. The transfer is through the Babak-Renggung-Rutus High Level Diversion (HLD) channel (18 km) and the Jangkok-Babak-Jurang Sate channel (43 km), as well as 22 other channeling channels in / across the watershed (87 km). Until now, 12 watersheds are connected, namely: Meninting, Jangkok, Remening, Babak, Dodokan, Renggung, Pare, Rere, Palung, Moyot, Aikampat and Starfruit. The number of main structures for taking water (headwork or HW) in the watersheds include 3 dams (BD), 77 reservoirs (E), 355 dams (B), and 55 diversions in the Jangkok-Babak-Jurang Sate canal. A total of 487 HWs were intended to irrigate 98,878 ha of irrigated land in 432 Irrigation Areas (DI) and a little to supply raw water of 404 l / sec. In addition, there are 2442 l / sec raw water withdrawals directly from 42 points of springs which are spread in the watershed: Jangkok, Babak, Aikampat, Meninting Midang, Kelongkong Remening, Renggung, Rung and Starfruit. Analysis of reservoir operational performance using the Hashimoto method yields a coefficient of Reliability (R) = 100%, Resiliency (R) = 100%, and Vulnerability (V) = 0%. So based on this RRV value the reservoir operational performance is categorized as maximum sustainable